How Does AI Support Wound Care Management? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2015)
Wound care is a critical and often complex aspect of healthcare, with a significant impact on patient quality of life and healthcare system resources. Tradit...
Keywords: AI in Dermatology; Support; Wound; Management; Artificial Intelligence; Machine Learning; Deep Learning